Who is afraid of Christmas? The effect of Christmas and Easter holidays on psychiatric hospitalizations and emergencies—Systematic review and single center experience from 2012 to 2021 - Schneider, Else; Liwinski, Timur; Imfeld, Lukas; Lang, Undine E.; Brühl, Annette B. (Frontiers in Psychiatry, 2023)
Background: Major holidays such as Christmas and New Year’s Eve are regular occasions for get-togethers in families and other social groups. Socially, these days are often loaded with memories and expectations but also involve the potential for interpersonal tension and conflicts and disappointments. In addition, loneliness might also be most intense during these days. All these factors might lead to the expectation of increased mental distress and subsequently increased help-seeking in psychiatric contexts resulting in emergency psychiatric contacts, psychiatric hospitalizations, and even suicidal behaviour. But is there evidence for increased psychiatric emergencies and hospitalizations around the days of Christmas? Methods: The existing evidence is systematically reviewed here (studies in PubMed in English investigating annual and Christmas-related variations in suicide (attempts), psychiatric emergencies and hospitalizations, last search date 13.07.2022) and complemented by an analysis of acute admissions at the University Psychiatry Clinics Basel, Switzerland, around Christmas and Easter holidays compared to the other days of the year. Easter was chosen as a comparison holiday. Results: In 25 reviewed studies, Christmas holidays were not associated with increased utilization of emergency psychiatric services. In contrast, hospitalizations were lower on Christmas and other holidays than the rest of the year. Analysing the annual variation of 26,088 hospitalizations in our centre between 2012 and 2021 revealed the same pattern. Conclusion: The assumption of increased utilization of psychiatric emergency services on Christmas and other major holidays is not confirmed by multiple studies around the globe in various socio-cultural and medical settings. The study is registered in the international prospective register for systematic reviews (PROSPERO; 351057).